Differences Of Murratal Arrahman And Klenengan On The Quality Of Sleeping For Postpartum Mother - Ahmaniyah Ahmaniyah; Anni Annisa’ (JURNAL KEBIDANAN, 2020)
During the postpartum period, there were many difficulties in resting and disturbed sleep patterns in the first three days due to perineal pain, discomfort in the bladder and disorders of babies who often cry because of the transition period. in the postpartum period, the majority of mothers experience disturbed sleep patterns and sleep quality, namely sleep patterns and sleep duration. The aims of this study was to determine the differences in the quality of postpartum sleep that was given the Murratal Arrahman therapy with Klenengan music. The sample in this study were postpartum mothers on days 3 to 7 with normal type of delivery obtained from random simple sampling and this study was a quasy experiment with pre-test and post-test only with control group design and for the measurement of sleep quality using the Pittsburgh Sleep Quality Index (PSQI). Result study Sleep quality between the intervention group and the control group was not significantly different (P = 0.33). Likewise, the quality of sleep in each time interval between the intervention group and the control group showed a significant difference, where the P value 0.05 and conclusion there is a difference between the provision of arrahman and klenengan murratal therapy and it can affect the quality of sleep of postpartum mothers, namely the quality of sleep. postpartum mothers are better off.